The impact of government stimulus packages towards business survival during covid-19 among small and medium enterprises in Sabah - Mat Salleh Ayub; Mazalan Mifli; Azmi Majid (Asian Scholars Network, 2022)
The purpose of this study is to examine the impact of government fiscal stimulus packages amounting RM100 billion for SMEs during the first wave of covid-19 to provide greater assistance to SMEs in sustaining business operations and preserving jobs, as well as to support growth in current economic conditions. This paper analyses the business survival during Covid- 19 by examining two determinants, namely government grants and financial assistance. Total number of 150 questionnaires distributed and 120 were returned. The respondents were selected from SMEs directory database and those who have been participated in SME@University program. The data were collected and analysed using Statistical Package for the Social Science (SPSS 26) and SmartPLS to analyse, and hypothesis testing. The study confirms that there are significant and positive impact between government stimulus packages towards business survival among SMEs in Sabah. The findings of this study have useful implication to help strengthen the government business survival approaches to support SMEs in Sabah during the pandemic outbreak. This paper, apart from its contribution to the entrepreneurship research, has useful implications for government in managing Covid-19 stimulus packages to SMEs in Sabah.